The taxonomic placement of three fossil Fundulus species and the timing of divergence within the North American topminnows (Teleostei: Fundulidae) - Ghedotti, Michael J.; Davis, Matthew P. (Zootaxa, 2017)
The fossils species †Fundulus detillae, †F. lariversi, and †F. nevadensis from localities in the western United States are represented by well-preserved material with date estimations. We combined morphological data for these fossil taxa with morphological and DNA-sequence data to conduct a phylogenetic analysis and a tip-based divergence-time estimation for the family Fundulidae. The resultant phylogeny is largely concordant with the prior total-evidence phylogeny. The fossil species do not form a monophyletic group, and do not represent a discrete western radiation of Fundulus as previously proposed. The genus Fundulus diverged into subgeneric clades likely in the Eocene or Oligocene (mean age 34.6 mya, 53–23 mya), and all subgeneric and most species-group clades had evolved by the middle Miocene. †Fundulus lariversi is a member of subgenus Fundulus in which all extant species are found only in eastern North America, demonstrating that fundulids had a complicated biogeographic history. We confirmed †Fundulus detillae as a member of the subgenus Plancterus. †F. nevadensis is not classified in a subgenus but likely is related to the subgenera Plancterus and Wileyichthys.